2015
DOI: 10.4236/ojas.2015.52016
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Digestive Apparatus in <i>Oligoryzomys nigripes</i> (Rodentia, Sigmodontinae)

Abstract: Although the Genus Oryzomys is widely distributed in the Americas, there are very few published data on the morphology of this rodent group. Notably, in relation to the digestive apparatus, the data are sparse and fragmented. In addition, because rodents are important animal models, this information may be useful in recent and promising areas for applied studies, such as clinical, therapeutic, and surgical models. Here, we describe the morphological characteristics of the digestive system in Oligoryzomys nigri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…The reduced number of liver lobes are thus thought to be indicative of adaptations away from a proteinaceous diet and towards herbivory (Perrin & Curtis, 1980; Vorontsov, 1962). However, this idea does not support the observed reduction in the liver lobe number in some insectivorous rodents, such as Oligoryzomys nigripes (four lobes) and Acomys spinosissimus (five lobes), and the seven‐lobe liver in herbivorous otomyids (Borghesi et al, 2015; Perrin & Curtis, 1980).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The reduced number of liver lobes are thus thought to be indicative of adaptations away from a proteinaceous diet and towards herbivory (Perrin & Curtis, 1980; Vorontsov, 1962). However, this idea does not support the observed reduction in the liver lobe number in some insectivorous rodents, such as Oligoryzomys nigripes (four lobes) and Acomys spinosissimus (five lobes), and the seven‐lobe liver in herbivorous otomyids (Borghesi et al, 2015; Perrin & Curtis, 1980).…”
Section: Discussionmentioning
confidence: 98%
“…The mucosa of the rodents' oesophagus is comprised of a stratified squamous epithelium, which is of a keratinized or non‐keratinized type partially depending on dietary habits. Several insectivorous–omnivorous rodents do not have epithelial keratinisation (Borghesi et al, 2015; Igbokwe & Obinna, 2016; Oliver et al, 2010), whereas the keratinized layer can be found in herbivorous rodents that consume mainly grass and rough plant material (Kotźe et al, 2006; Scopin et al, 2015; Tammam et al, 2017). Like its relative, S. leucodon , C. badius possessed a keratinized epithelium, which may protect the oesophageal mucosa from food abrasion (Scopin et al, 2015; Sokołowska et al, 2021), bacteria invasion (Squier & Kremer, 2001) and gastric juice during regurgitation (if present).…”
Section: Discussionmentioning
confidence: 99%
“…Rodent GITs have highly specific morphological, histological, and functional traits that have developed over time to accommodate these environmental variations. That includes the esophagus and stomach, among its most important vital parts (Borghesi et al, 2015;Zhang et al, 2022). The esophagus is a narrow muscular folded tube connected the pharynx to the stomach's cardio in a direct line, and it travels through the cervical region and the thoracic cavity…”
Section: Introductionmentioning
confidence: 99%
“…O desenvolvimento do sistema esquelético tem sido alvo de estudos que buscam compreender não apenas o desenvolvimento normal (Abzhanov et al 2007, Kaufman 2011, mas também as influências de drogas e medicamentos que possam interferir na formação, crescimento e fisiologia do esqueleto (Teixeira et al 2010, Cheng et al 2014, bem como descrições no individuo adulto podem contribuir para o conhecimento sobre a funcionalidade dos diferentes sistemas corpóreos (Borghesi et al 2015).…”
Section: Introductionunclassified